The Influence of The Application of The Discussion Method on The Learning Motivation of Intensive PAI Semester IV Students in PAI Learning Planning and Design Courses - Uswatun Hasanah; Nurlaela Rusdin (Penerbit Hellow Pustaka, 2025)
Applying the discussion method in presentations can provide motivation to always express opinions and strengthen arguments. By expressing our opinions we can find out what people in this world think. A discussion is a scientific meeting to exchange ideas about a problem. This research aims to determine whether there is an effect of applying the discussion method on the learning motivation of intensive PAI students in the fourth semester in the PAI learning planning and design course. This research uses a causative type of quantitative research method which consists of two variables, namely the application of the discussion method (variable X) and learning motivation (variable Y). The collection technique was by distributing questionnaires for variables X and Y, and questionnaires as support, while the subjects of this research were taken from 20 respondents. For data analysis used is the critical price table r and calculated using SPSS 25 with a simple linear regression formula. The research results show that the application of the discussion method has a positive influence on learning motivation. This is proven by the T test result value which shows tcount > ttable (2.541>2.100). The R square value of the learning motivation variable is 16%, while the remaining 84% is influenced by other variables outside the research.